2012
DOI: 10.1111/j.1532-849x.2012.00908.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mandibular Bone Mineral Densities in Dentate and Edentulous Patients

Abstract: Comparison of the mandibular body BMD revealed that dentate patients had less dense bone than the edentulous patients. Further investigations are needed to determine the BMD of the jaws in different regions and for different systemic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
1
3
0
1
Order By: Relevance
“…The findings of the study showed the mean mandibular body BMD value of 1.294±0.21 g/cm 2 in the control group and 1.247±0.22 g/cm 2 in all the participants in our study which is similar to the findings of Buyukkaplan et al 20 (1.10±0.31 g/cm 2 ), Pluskiewicz et al 22 (1.221±0.3 g/cm 2 ), Devlin and Horner 23 (1.15±0.26 g/cm 2 ), Drage et al 24 (1.38±0.39 g/cm 2 ), and Esfahanizadeh et al 21 (1.386±0.320 g/cm 2 ). Different BMD values in studies may be associated with “region of interest (ROI)” or dentulous/edentulous patients.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the study showed the mean mandibular body BMD value of 1.294±0.21 g/cm 2 in the control group and 1.247±0.22 g/cm 2 in all the participants in our study which is similar to the findings of Buyukkaplan et al 20 (1.10±0.31 g/cm 2 ), Pluskiewicz et al 22 (1.221±0.3 g/cm 2 ), Devlin and Horner 23 (1.15±0.26 g/cm 2 ), Drage et al 24 (1.38±0.39 g/cm 2 ), and Esfahanizadeh et al 21 (1.386±0.320 g/cm 2 ). Different BMD values in studies may be associated with “region of interest (ROI)” or dentulous/edentulous patients.…”
Section: Discussionsupporting
confidence: 91%
“…Another factor might be tooth loss with ageing, for which some authors found a positive correlation with mandibular BMD. 24 Drozdzowska et al 20 evaluated mandibular radiographic indices in post-menopausal edentulous females and found that the MCI was not suitable to distinguish normal from osteopenic/osteoporotic patients. This finding is in contrast with ours but may reflect the use of different samples.…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmaların çoğu kesitsel olmakla birlikte, östrojen replasman tedavisinin etkisini inceleyen 5 yıllık longitudinal bir çalışma, omurga ve el bileği KMY'si ile bağlantılı olarak mandibuler kemik kütlesinde de önemli iyileşme olduğunu göstermiştir [34]. Aksine, sistemik KMY değerlendirilmeksizin erkeklerin ve yaş, cinsiyet ve eksik diş sayısı dağılımı açısından erkeklere oranla farklılık göstermeyen kadınların (menopozdan bağımsız olarak) dahil edildiği bir kesitsel çalışmada, dişli hastalar dişsiz hastalara oranla daha düşük mandibular KMY değerleri göstermişlerdir [35]. Tüm kırıkların %70'i osteoporotik kadınlarda meydana geldiğinden [4] ve osteoporozun ağırlıklı olarak menopoz sonrası östrojen eksikliği ile ilişkili olduğuna dair geleneksel görüş nedeniyle, çoğu çalışmanın menopoz sonrası kadınlara odaklanması şaşırtıcı değildir.…”
Section: Osteoporoz Ve Alveolar Kemik Kaybı Arasındaki Korelasyonunclassified